Late Orthodontic Prosthetic Therapy with the Use of Delair Mask - J. Racek; L. Cupal; T. Dostálová (Czech Dental Chamber, 2006)
The adjustment of diastema and trema in complete set of dentition is not easy and requires an interdisciplinary approach. Conspicuous gaps at visible part of dentition represent a distractive or worrisome aesthetic handicap with negative influence on the individual's psyche and frequently also on the function of dentition. The presumption of the treatment success is the occlusion or substantial diminution of the trema with improved aesthetic appearance and removal of gnatologic interferences. In the case report the authors present good experience with the occlusion of trema at the adult age by orthodontic therapy, fixed apparatus and Delair mask with subsequent prosthetic solution. Emphasis is placed on a stable result, biological approach with minimal invasive procedures. The requirement and idea of the patient belong to basic principles of therapeutic plan.